2019
DOI: 10.1002/ecy.2677
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation, forest structure, and topography modulate impacts of drought in a tropical forest landscape

Abstract: Climate models predict increases in drought conditions in many parts of the tropics. Yet the response of tropical forests to drought remains highly uncertain, especially with regards to the factors that generate spatial heterogeneity in drought response across landscapes. In this study, we used Landsat imagery to assess the impacts of a severe drought in 2015 across an ~80,000‐ha landscape in Puerto Rico. Specifically, we asked whether drought effects varied systematically with topography and with forest age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 98 publications
(223 reference statements)
0
38
0
Order By: Relevance
“…Despite our experimental design that purposefully limited phenotypic range by focusing on species within a single genus, species show strong trait differentiation along the two main functional dimensions, suggesting that they occupy distinct niche space both in terms of leaf physiology and leaf economics. As the four focal Micropholis species have contrasting habitat preferences, such strong trait differences between species may play a role in local biotic interactions and shape species distributions across environmental gradients (Fortunel et al , ; Schwartz et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite our experimental design that purposefully limited phenotypic range by focusing on species within a single genus, species show strong trait differentiation along the two main functional dimensions, suggesting that they occupy distinct niche space both in terms of leaf physiology and leaf economics. As the four focal Micropholis species have contrasting habitat preferences, such strong trait differences between species may play a role in local biotic interactions and shape species distributions across environmental gradients (Fortunel et al , ; Schwartz et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…An important challenge to strengthen predictions for how tropical forests will respond to climate change is to improve our understanding of how multiple factors shape tropical tree response to water and nutrient availability (Condit et al, 2013;Fortunel et al, 2016;Uriarte et al, 2018;Schwartz et al, 2019). Functional traits allow examining species distributions across broad environmental gradients only in that we assume traits to be tightly linked to the underlying key physiological processes driving species response to the environment (Violle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we limited our study area (312,319 ha) to forested areas in Puerto Rico [65][66][67] . Field plots [68][69][70][71] cover the rainfall distribution, elevation gradients and two dominant geologies (volcanic and limestone), that are reflected in the diversity of forest characteristics present in Puerto Rico (Fig. 1, Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The landscape diversity has also changed in areas where forests have changed significantly (e.g., Shanghai, Changzhi, and Jincheng). spatial patterns (such as patch fragmentation, landscape diversity, and spatial aggregation) [13][14][15][16] and the relationship between LUCC and ecological processes [17][18][19][20].Edurne et al used several Landsat TM images for different months of 1987 and 2010 to assess the forest cover change of the Natural Natural Park (Spain) based on remote sensing and landscape metrics. The results showed that the change of forest cover in the region leaded to the increase of landscape fragmentation, and they believed that the spatial and temporal changes of tree species distribution in forests were closely related to the landscape structure [21].…”
mentioning
confidence: 99%
“…The landscape diversity has also changed in areas where forests have changed significantly (e.g., Shanghai, Changzhi, and Jincheng). spatial patterns (such as patch fragmentation, landscape diversity, and spatial aggregation) [13][14][15][16] and the relationship between LUCC and ecological processes [17][18][19][20].…”
mentioning
confidence: 99%